IKLAN CALON PRESIDEN DAN MINAT MEMILIH (Studi Perbandingan Iklan Prabowo Subiyanto, Hatta Rajasa dan Joko Widodo,Yusuf Kalla Sebagai Calon presiden di TV ONE dan Metro TV Terhadap Minat Memilih di Kalangan Masyarakat Dukuh Jurangsari, Desa Juron, Kecamata - Muchammad Ridwan, Tutut (Transformasi, 2014)
The advertisement about Prabowo and Jokowi are certainly aimed at influencing society to choose who to be president during the presidential election in June 2014. Various media advertising can be through print and electronic media. Prabowo is supported by Aburizal Bakrie owner of ANTV and TV One often advertises himself as a presidential candidate, meanwhile Joko Widodo supported by Surya Paloh owner of television station Metro TV that has also frequently serve ads candidate JokoWidodo. This research uses the theory of media massa. The results of there search showed that the presence of effect advertising on interest choose between Prabowo and Jokowi equally affect the interest of selecting the value of 2,606 to influence Prabowo Ads with value of p 0.011 (p<0.05). And also value of 2,909 to influence Jokowi Ads with value of p 0.005 (p <0.05). Seeing the effectiveness of the ads seen from the magnitude of the highest t value affecting interest Jokowi advertising of Jokowi higher than Prabowo. The influence of advertising in the presidential election this time of 0.091 is seen from the value of R2, which means that the effect is only 0.9% in the increasing interest in selecting the remaining 91% are other factors not examined here. Keyword: election; effectiveness; advertising